2020
DOI: 10.1099/ijsem.0.004476
|View full text |Cite
|
Sign up to set email alerts
|

Azoarcus halotolerans sp. nov., a novel member of Rhodocyclaceae isolated from activated sludge collected in Hong Kong

Abstract: A floc-forming bacterial strain, designated HKLI-1T, was isolated from the activated sludge of a municipal sewage treatment plant in Hong Kong SAR, PR China. Cells of this strain were Gram-stain-negative, strictly aerobic, catalase- and oxidase-positive, rod-shaped and motile by means of a single polar flagellum. Growth occurred at 18–37 °C (optimum, 28 °C), pH 5.5–9.0 (optimum, pH 7.5) and with 0–8.0 % (w/v) NaCl (optimum, 1–1.5 %) concentration. The major fatty acids of strain HKLI-1T were C16 : 0 and summed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The description is as for Azoarcus halotolerans ( Li et al, 2020 ). The type strain is HKLI-1 T (= KCTC 72659 T =CCTCC AB 2019312 T ).…”
Section: Discussionmentioning
confidence: 99%
“…The description is as for Azoarcus halotolerans ( Li et al, 2020 ). The type strain is HKLI-1 T (= KCTC 72659 T =CCTCC AB 2019312 T ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA-DNA hybridization (DDH) values were estimated online using formula 2 of the Genome-to-Genome Distance Calculator 2.1 (GGDC; http://ggdc.dsmz.de/ggdc.php) as described by Wang et al [12]. Orthologous average nucleotide identity (ANI) values were calculated online on the EZBioCloud sever ( www.ezbiocloud.net/tools/ani) as described by Li et al [13]. Average amino acid identity (AAI) values were calculated online by using the AAI calculator by the Kostas lab (http://enve-omics.ce.gatech.edu/aai/).…”
Section: Genomic Analysismentioning
confidence: 99%
“…Overexpression of PEP-CTERM A protein (PepA) could circumvent the requirement of PrsK and PrsR for floc-formation [19]. We had also demonstrated that one of the four RpoN paralogues, RpoN1, regulated the floc formation but not exopolysaccharide biosynthesis in a floc-forming Aquincola tertiaricarbonis RN12 strain [18] and Azoarcus halotolerans [21]. The synthesized exopolysaccharide chains were not tightly bound to the bulk of cell aggregates but were released into the cultivation broth.…”
Section: Introductionmentioning
confidence: 99%